Bibliometric analysis of the effects of mental fatigue on athletic performance from 2001 to 2021 - Chen, X.-X.; Ji, Z.-G.; Wang, Y.; Xu, J.; Wang, L.-Y.; Wang, H.-B. (Frontiers in Psychology, 2023)
Aims: To explore the research hot topics and main contents in the field of the influence of mental fatigue on athletic performance, and to provide new ideas and directions for future research in this field.